Incidental finding of combined jugular phlebectasia and carotid medialization in a patient with severe kyphosis - Bader J. Alharthi; Essam A. Elgamal; Eman R. Salima; Nada M. Althomali; Mohamed I. Elgamal (Egyptian Journal of Chest Disease and Tuberculosis)
Out of the previously published case studies, this is the first case presentation of combined vascular anomalies, including right internal jugular vein phlebectasia and left internal carotid artery medialization in a patient with severe kyphosis. A condition associated with a double risk of fatal arterial and venous hemorrhages from surgical and nonsurgical interventions.